Smartphone-based Data Acquisition Method for Modelling 3D Printed Arm Casts - Van, Tuong Nguyen; Le Thanh, Truong; Van, Trong Nguyen; Naprstkova, Natasa (Manufacturing Technology Journal, 2023)
In recent years, 3D printed arm casts can replace traditional arm casts to treat bones fractures. 3D printed arm cast modelling often uses professional 3D scanning systems to capture 3D data of the arm. These systems are very expensive and may not be available in many hospitals. In order to over-come this disadvantage, inexpensive methods should be developed. This paper introduces a new data collection method based on smartphones. The photos of an arm were taken with a smartphone cam-era using some special techniques that could facilitate the process of image processing and 3D mod-elling in Agisoft Metashape and CATIA. To validate the proposed method, the photogrammetric model was compared with the scanned model (obtained by a low cost scanner) in GOM Inspect. Be-sides, a fit check of real 3D printed arm casts attached on the volunteer's forearm was also per-formed. The test results indicate that the photogrammetric model could be used as raw data for 3D arm modelling.
Keywords: Photogrammetry; 3D printed; Arm cast; Smartphone; Data acquisition